The role of prostate cancer biomarkers in undiagnosed men. Issue 3 (May 2017) - Dani, Hasan; Loeb, Stacy
Abstract : Purpose of review: This article intends to review biomarkers derived from blood, urine, and tissue that can aid in the diagnosis of prostate cancer (PCa). Recent findings: PCa screening requires tools that complement prostate-specific antigen (PSA) with a higher specificity for clinically significant disease. Novel blood biomarkers, such as the Prostate Health Index (phi) and 4Kscore, utilize isoforms of PSA to more accurately predict high-grade PCa than traditional tools such as PSA and the percentage free-to-total PSA. Several gene products associated with PCa can be detected in the urine through commercially available assays. PCa antigen 3 (PCA3), though approved for repeat biopsy decisions, appears inferior to other biomarkers such as phi for identifying aggressive disease. However, combinations of PCA3 with other urine assays have shown promising results. One tissue-based hypermethylation test, named ConfirmMDx, can also be used to determine the need for repeat biopsy in men with a prior negative biopsy. Summary: Several biomarkers have been developed to aid in the screening and diagnosis of PCa. Such tests are often indicated in men with moderately elevated PSA or history of a prior negative biopsy. Their use facilitates reduction of unnecessary biopsies without sacrificing the early diagnosis of clinically significant PCa.